Education, Political Party, and Football Viewership Predict Americans' Attention to News About Concussions in Sports - Lindner, Andrew M.; Hawkins, Daniel N. (Frontiers in Sports and Active Living, 2021)
News outlets, sports coverage, and even Hollywood movies have highlighted the growing body of research documenting the long-term negative consequences of traumatic injury in athletics, particularly, (sports-related) concussions. Despite so much media coverage, little is known about how much attention members of the American public pay to sports concussion news. Disparities in attention to concussion news among sociodemographic groups may contribute to further inequalities in rates of concussions that stem from participation in collision sports. In this study, using a 2017 nationally representative survey of US residents (n = 964), we examine the social, political, and demographic correlates of individuals' attention to news about concussions in sports. Regression results indicate that older, more educated, Democratic-leaning respondents reported that they pay more attention to news about concussions. Additionally, respondents with a greater past competitive athletic participation and those who regularly watch baseball and football reported higher levels of attention to concussion news. These findings are consistent with previous research showing higher levels of news consumption and trust in science among the highly educated and Democrats. The increased levels among football viewers may be in response to the inclusion of concussion news in game coverage.